Lignin-g-polycaprolactone as a form-stable phase change material for thermal energy storage application. (15th December 2022) - Lee, Johnathan Joo Cheng; Sugiarto, Sigit; Ong, Pin Jin; Soo, Xiang Yun Debbie; Ni, Xiping; Luo, Ping; Hnin, Yu Yu Ko; See, Josephine Si Yu; Wei, Fengxia; Zheng, Rongyan; Wang, Pei; Xu, Jianwei; et al.
Abstract: Lignocellulosic biomass is mostly found in municipal waste by-products, and a major component of this waste is made up of the macropolymer, lignin, which is usually hard to valorize and causes environmental pollution issues. Valorizing lignin through their hydroxy groups has been intensively researched for various purposes and therefore, is a promising green alternative sustainable material. Lignin can be used as a composite phase change material (PCM) as compared to conventional organic and inorganic PCMs. In this work, Lignin-g-polycaprolactone (PCL) was prepared by grafting of alkaline lignin with PCL via the ring-opening polymerization reaction using triazabicyclodecane (TBD) as an organic catalyst. A comparison study of the physically mixed lignin with PCL, and Lignin-g-PCL was conducted to investigate the differences in their thermophysical properties. The chemical structure of Lignin-g-PCL was verified by nuclear magnetic resonance (NMR), and the products were separated by molecular weight via gel permeation chromatography (GPC), revealing the PCL was successfully grafted onto the lignin via the ring-opening polymerization. Differential scanning calorimetry (DSC) results showed that the phase transition temperature of Lignin-g-PCL was approximately 51.3 °C, with a latent heat value of 61.16 J/g. Thermal cycling test up to 100 cycles also revealed its thermal stability and reliability in applications. Thermogravimetric analysis (TGA) confirmed its thermal degradation temperatures at 300–400 °C which was much higher than its melting temperature 51.3 °C. Lignin-g-PCL also showed superior form stability in contrast to both its pristine counterparts and physically mixed samples based on a form stability and leakage test. Lastly, Lignin-g-PCL demonstrated its potential application as a PCM via a thermal absorption test where its solid-solid phase change was most apparent during cooling and was able to exhibit thermoregulation of about 2 min at near body temperature of about 39 °C.